A Comparative Study on the Contralateral Supression Effects of Acoustic Stimulations on Otoacoustic Emissions - Amir Abbas Ebrahimi; Seyyedeh Mahnaz Ahmadi; Saeed Sarough-Farahani; Soghrat Faghih-Zadeh; Yousef Salim-Pour; Razieh Zenouzi (University of Social Welfare and Rehabilitation Sciences, 2004)
Objective: Acoustic stimulation of auditory efferent system causes contralateral shift in the OAEs amplitude. In this study the contralateral suppression effect of pure tone & NBN at center frequencies of 1, 2 & 4 kHz Frequencies has been evaluated in the right ears of normal 19 to 27 years old adults.  Materials & Methods: The data were elicited from 37 subjects (15 males & 22 females) with normal hearing who participated in this study. After determining the level of NBN by loudness adjustment between pure tone at 70 dBHL at 1, 2 & 4 kHz in left ear, EOAEs was measured using tone burst at central frequencies of 1, 2 & 4 kHz in right ear. Then the amplitude shift of TBEOAEs was evaluated at the presence of contralateral pure tone & NBN stimuli. Results: There was a significant shift in the amplitude of TBEOAEs by contralateral stimulation of pure tone & NBN which was greater in NBN. The magnitude of amplitude shift was become greater at high frequencies of contalateral stimuli. Conclusion: There was a decrease in the amplitude of TBEOAEs by contralateral stimulation and the stimulus with greater frequency band had geater effects on contralateral suppression. The impact of this effect was highly depend on the spectrum & frequency of contralateral stimuli.